Xanthomonas spp. Infecting Araceae and Araliaceae: Taxonomy, Phylogeny, and Potential Virulence Mechanisms - Shu-Cheng Chuang; Shefali Dobhal; Lisa M. Keith; Anne M. Alvarez; Mohammad Arif (Biology)
The genus Xanthomonas (family Xanthomonadaceae) comprises 39 validly published species and is associated with a broad host range, infecting hundreds of monocot and dicot plants worldwide. While many Xanthomonas species are notorious for causing leaf spot and blight diseases in major agricultural crops, less attention has been given to their impact on ornamental plants. In Hawaii and other key production regions, xanthomonads have posed persistent threats to popular ornamentals in the Araceae and Araliaceae families. This review synthesizes the evolving phylogenetic and taxonomic framework of Xanthomonas strains isolated from Araceae and Araliaceae, highlighting recent advances enabled by multilocus sequence analysis and whole genome sequencing. We discuss the reclassification of key pathovars, unresolved phylogenetic placements, and the challenges of pathovar delineation within these plant families. Additionally, we examine current knowledge of molecular determinants of pathogenicity, including gene clusters involved in exopolysaccharide and lipopolysaccharide biosynthesis, flagellar assembly, cell-wall-degrading enzymes, and secretion systems (types II, III, and VI). Comparative genomics and functional studies reveal that significant gaps remain in our understanding of the genetic basis of host adaptation and virulence in these xanthomonads. Addressing these knowledge gaps will be crucial for developing effective diagnostics and management strategies for bacterial diseases in ornamental crops.